PERLINDUNGAN HUKUM TERHADAP PELAKU TINDAK PIDANA ABORSI - Deshaini, Liza; Oktarina, Evi (Solusi, 2020)
Legal Protection for Abortion Criminals is the suspect has the right to immediately be examined by the investigator and can then be submitted to the public prosecutor, the suspect has the right to have his case immediately brought to trial by the public prosecutor, the defendant has the right to be tried immediately by the court. and factors that cause abortion are economic factors, hereditary diseases, psychological factors, age factors, actors of maternal diseases, other factors.